2015
DOI: 10.1097/bpo.0000000000000260
|View full text |Cite
|
Sign up to set email alerts
|

Does Preoperative Orientation and Education Alleviate Anxiety in Posterior Spinal Fusion Patients? A Prospective, Randomized Study

Abstract: Level I study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 9 publications
0
28
1
8
Order By: Relevance
“…In turn, presence of postoperative anxiety turned out to be a significant predictor of less satisfaction with analgesia. However, Rhodes et al 29 showed that patients who were given preoperative education -the intervention group -reported higher anxiety levels during the postoperative interval and higher satisfaction at discharge than patients from the control group. Royse et al 30 observed that only the nociceptive domain (pain or nausea) influenced satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, presence of postoperative anxiety turned out to be a significant predictor of less satisfaction with analgesia. However, Rhodes et al 29 showed that patients who were given preoperative education -the intervention group -reported higher anxiety levels during the postoperative interval and higher satisfaction at discharge than patients from the control group. Royse et al 30 observed that only the nociceptive domain (pain or nausea) influenced satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Research examining education interventions prior to surgery indicate that delivery of education alone without providing coping skills may actually increase anxiety and distress 23 . Limited research has examined interventions providing coping strategies for adolescents undergoing major surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other studies, the correlation between the information and anxiety variables was negative and weak but not statistically significant in this study. Rhodes et al (2015) concluded that patients required age-appropriate information and educational strategies to minimize preoperative anxiety. The results obtained in this study may be explained by the fact that most of the sampled patients had undergone previous surgeries, increasing the likelihood of having a higher level of knowledge.…”
Section: Discussionmentioning
confidence: 99%